Survey on Energy-Aware Cloud Computing Algorithms: A Review - Garg, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an elastic model which is used to satisfied changing needs of users. It provides pay as you go services (PaaS, SaaS, and IaaS) to the users. The growing trend of cloud computing has raises the concern of energy efficiency in cloud computing because a data center consumes lots of energy and emits carbon-dioxide in the environment. Today, the main focus of researcher has been diverted from cloud resource management to energy management. Various algorithms on VM allocation, migration, task scheduling and load balancing have been developed to ensure minimum energy dissipation in cloud data center. The main focus of this paper is study the existing algorithms and to analysis the best algorithms